2014
DOI: 10.1007/s10488-014-0540-x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Hospital Discharges and Dispositions for Episodes of Co-occurring Severe Mental Illness and Substance Use Disorders

Abstract: This study examined trends in general hospital discharges and dispositions involving episodes of severe mental illness (SMI) with and without co-occurring substance use disorders. We analyzed data from the National Hospital Discharge Survey from 1979 through 2008. Discharges involving SMI and co-occurring substance use disorders (COD) were associated with shorter lengths of stay and had a greater likelihood of being discharged routinely or home and reduced likelihood of being transferred to a short- or long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
2
5
1
Order By: Relevance
“…The most common disposition outcome was being discharged home, which is consistent with extant research that documents comparable rates of being discharged home, ranging from 54% to 88%, depending on the sample population [25, 42, 43]. Confirming part of our hypothesis, we found that men were less likely to be discharged home than women.…”
Section: Discussionsupporting
confidence: 90%
“…The most common disposition outcome was being discharged home, which is consistent with extant research that documents comparable rates of being discharged home, ranging from 54% to 88%, depending on the sample population [25, 42, 43]. Confirming part of our hypothesis, we found that men were less likely to be discharged home than women.…”
Section: Discussionsupporting
confidence: 90%
“…Our results are somewhat different compared to the recent time-trend studies elsewhere. In a hospital discharge study from the United States, the co-occurring problems had distinctly increased over the 20 year period [17]. In our study, no such overall trend was observed.…”
Section: Discussioncontrasting
confidence: 71%
“…The individuals with both disorders had, for example, multiple visits to emergency departments [8] and increased rates of psychiatric hospitalisation [15,16]. In the United States, the comorbid population had shorter lengths of hospital stay, a greater likelihood of being discharged routinely, and reduced likelihood of being transferred to a short-or long-term facility, indicating an increasing trend of a 'revolving door syndrome' [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 In addition, mental disorders and substance use disorders often cooccur, and co-occurrence increases the risk of homelessness, incarceration, relapses, chronic medical conditions, and hospital readmission. [8][9][10][11][12][13][14] A study of hospitalization trends in the United States showed that the percentage of hospitalizations related to severe mental illness increased from 1.28% in 1979 to 2.96% in 2008, and the percentage of hospitalizations with co-occurring mental disorders and substance use disorders increased steadily from 0.07% in 1979 to 1.13% in 2008. 8 In addition, mental disorders and substance use disorders pose special risks for the health and well-being of women of reproductive age and their families.…”
mentioning
confidence: 99%